Representation of Madurese Dialects in English Study Program Students at Universitas Trunojoyo Madura - Wahyudi, Muhammad Arman Indra; Halili, Mohammad (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
AbstarctThis paper aims to identify the Madurese dialects and identify difficult factors for the English study program at Universitas Trunojoyo Madura in understanding Madurese dialects. The communicative goals to some extent are unachievable as the speakers and listeners do not share lexical variation understanding even though they come from the same linguistic background. This applied a qualitative method with a descriptive approach. Represented participants from each district (Bangkalan, Sampang, Pamekasan, Sumenep) engaged in this paper. They filled out a designed questionnaire shared through Google Form. To analyze the chosen data, the proposing theoretical framework proposed by Wardhaugh, looking at the interwoven between the speaking linguistic data and existing theories. The result of this paper shows that there are lexicon variations of Madurese dialects including nouns, pronouns, adjectives, verbs, and adverbs and there are also difficult factors for English Study Program students at the University of Trunojoyo Madura in understanding the Madurese dialect, including the vocabulary factor, which referred to the number of lexical variations (special words) of the Madurese dialect and the pronunciation factor, which referred to the speed of intonation and accent. Keywords: English study program, Madurese dialect, Representation